Farmer reported pest and disease impacts on root, tuber, and banana crops and livelihoods in Rwanda and Burundi - Okonya, J.; Ocimati, W.; Nduwayezu, A.; Kantungeko, D.; Niko, N.; Blomme, Guy; Legg, James P.; Kroschel, Jürgen (MDPI, 2019)
Biotic constraints cause major crop losses and, hence, food insecurity in sub-Saharan Africa. This study documented the popularity, production constraints, pests and diseases, farmers’ perceptions on the severity of biotic constraints and the impact of related crop losses on household food security for the key root, tuber and banana (RTB) crops (cassava, potato, sweetpotato and banana). Farmer interviews were conducted in 2014 covering 811 households in Rwanda and Burundi. Farmers were asked to list their RTB crop production constraints, name insect pests and diseases of RTB crops, estimate crop loss due to pests and diseases, and mention if their household experienced any form of food insecurity due to pests and diseases. Cutworms and late blight in potato, banana weevils and banana Xanthomonas wilt in banana, cassava whitefly and cassava mosaic disease in cassava, sweetpotato weevils, and sweetpotato virus disease in sweetpotato were the most predominant pests and diseases reported. Crop losses due to pests and diseases for sweetpotato, banana, potato and cassava were estimated at 26%, 29%, 33%, and 36%, respectively, in Rwanda and 37%, 48%, 38%, and 37% in Burundi. Pests and diseases reduce the profitability of RTB crops, threaten food security, and constitute a disincentive for investment. Sustainable and affordable integrated pest management packages need to be developed.